Social support criteria in vascularized composite allotransplantation versus solid organ transplantation: Should the same ethical considerations apply? - Kimberly, Laura L.; Onuh, Ogechukwu C.; Thys, Erika; Rodriguez, Eduardo D. (Frontiers in Psychology, 2022)
The field of vascularized composite allotransplantation (VCA) has evolved rapidly, with some procedures poised to transition from highly experimental research toward standard of care. At present, the use of social support as an eligibility criterion for VCA candidacy is at the discretion of individual VCA programs, allowing VCA teams to consider the unique needs of each potential candidate. Yet this flexibility also creates potential for bias during the evaluation process which may disproportionately impact members of certain communities where social configurations may not resemble the model considered ‘optimal.’ We examine the extent to which ethical considerations for social support in solid organ transplantation (SOT) may be applied to or adapted for VCA, and the ethically meaningful ways in which VCA procedures differ from SOT. We conclude that VCA programs must retain some flexibility in determining criteria for candidacy at present; however, considerations of equity will become more pressing as VCA procedures evolve toward standard of care, and further empirical evidence will be needed to demonstrate the association between social support and post-operative success. The field of VCA has an opportunity to proactively address considerations of equity and justice and incorporate fair, inclusive practices into this innovative area of transplantation.